2018
DOI: 10.1016/j.jsxm.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Deviance or Normalcy? The Relationship Among Paraphilic Thoughts and Behaviors, Hypersexuality, and Psychopathology in a Sample of University Students

Abstract: Introduction The actual definitions of paraphilic thoughts or behaviors and hypersexuality are still a matter of debate in the scientific community, and few studies have evaluated their psychopathological correlates in non-clinical samples of both men and women. Aim This study aimed at shedding light on the gender differences in terms of frequency of paraphilic fantasies and behaviors, and the relationship among paraphilias, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 40 publications
5
52
0
4
Order By: Relevance
“…123 The results of another study showed a positive correlation between sexual compulsivity and both anxious and avoidant attachment. 125 Finally, one study showed an association between childhood adversities and CSB among women, 123 and another four studies revealed a relationship between sexual compulsivity and child sexual abuse (CSA). [135][136][137][138] Prior works have found a significant relationship between CSA and insecure attachment [171][172][173] and demonstrated their high prevalence among individuals with CSB symptoms.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…123 The results of another study showed a positive correlation between sexual compulsivity and both anxious and avoidant attachment. 125 Finally, one study showed an association between childhood adversities and CSB among women, 123 and another four studies revealed a relationship between sexual compulsivity and child sexual abuse (CSA). [135][136][137][138] Prior works have found a significant relationship between CSA and insecure attachment [171][172][173] and demonstrated their high prevalence among individuals with CSB symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the result suggesting CSB (assessed by SAST-R) 98 being less present among women regardless of the history of sexual abuse, authors have, however, found that participants (both men and women) with a history of CSA reported more attachment anxiety in romantic relationships than those without a history of CSA. Castellini and colleagues' study 123 revealed an association between childhood adversities (assessed by The Childhood Experience of Care and Abuse) 139 and CSB (assessed by Hypersexual Disorder Screening Inventory) 128 among women, but not among men.…”
Section: Traumatic Experiencesmentioning
confidence: 95%
See 2 more Smart Citations
“…Männer zeigten eine höhere Prävalenz für Voyeu rismus, Exhibitionismus, Masochismus und Frotteurismus, Frauen für Fetischismus und Masochismus. Die Ausbildung von Paraphi lien bei Männern zeigte einen Zusammenhang mit Hypersexua lität, bei Frauen mit sexuellen Übergriffen in der Kindheit [8]. Zu einem ähnlichen Ergebnis kam ein Forscherteam in Kanada.…”
Section: Qualitative Veränderungen Sexueller Vorliebenunclassified